FRASA NOMINA ENDOSENTRIS BAHASA PONOSAKAN (ENDOSENTRIC NOUN PHRASE IN PONOSAKAN LANGUAGE) - Oldrie Ch. Sorey (Balai Bahasa Sulawesi Utara, 2016)
The study is aimed to describe endocentric noun phrase of Ponosakan language. The issue that is analyzed in the study deals with type, category, and relation of meaning on the endocentric noun phrase of Ponosakan language. The issue is analyzed by referring to the theory of Zaenal Arifin and Junaiyah. The method used in this study is qualitative descriptive method. The result shows that endocentric nominal phrase of Ponosakan language covers coordinative phrase, phrase attributive, and appositive phrase. Categories of endocentric noun phrase found, among which, noun + noun, noun + verb, noun + adjective, noun + numeral, numeral + noun, noun + adverb, noun + preposition, noun + determiner, while the meanings among elements of endocentric noun phrase of Ponosakan, i.e. additional meaning, selection meaning, clarification meaning, limitation meaning, and meaning of determiner or indicator.